The Ship Must Cast Off: Indonesia’s Perspective And Contribution On The New Biodiversity Agreement - Romdoni, Rafi Nasrulloh Muhammad (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
“The ship has reached the shore” was Rena Lee’s remarkable statement as it symbolized the adoption of the new agreement on biodiversity beyond national jurisdiction (BBNJ Agreement) in the first quarter of 2023. Immediate action to deal with biodiversity loss while at the same time synchronizing States’ interests (developed v. developing) regarding certain activities in area beyond national jurisdiction (ABNJ) were the tough challenges during the process. Indonesia has been participating actively in the development of international law of the sea, including the BBNJ Agreement. By using normative legal research, this article explores the perspective and contribution of Indonesia on the protection of biodiversity in ABNJ, as well as the next steps the Government of Indonesia (GoI) should take. The result shows that Indonesia has always been a persistent contributor to the law of the sea, including the BBNJ Agreement. Also, Indonesia must commence some preparations such as synchronizing national laws, strengthening cooperation and finally ratify the Agreement.